Children of Alcatraz : growing up on the rock - Murphy, Claire Rudolf (Walker & Co. : Distributed to the trade by Holtzbrinck Publishers, 2006)
Illustrated photographs and essays profile generations of children who grew up on Alcatraz Island; and contains personal stories and interviews with surviving Alcatraz kids.